PENGEMBANGAN MODUL AJAR PENDIDIKAN PANCASILA BERBASIS PjBL UNTUK MENINGKATKAN KARAKTER BERNALAR KRITIS DAN KEMANDIRIAN SISWA KELAS V SD - Purba, Juliana; Y. B. Adimassana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical reasoning and independence character of fifth grade elementary school students based on the results of interviews with class teachers and the results of the initial character questionnaire analysis followed by 29 fifth grade elementary school students. The purpose of this research is to develop a Project-based Pancasila Education Learning Module that is feasible and high-quality to improve students' critical reasoning and independence character. The research method used is R&D with the ADDIE development model. The research subjects consisted of 1 fifth grade elementary school teacher and 29 fifth grade elementary school students. There are research objects, namely the PjBL based Pancasila Education open module, critical reasoning character, and independence character. Data collection techniques used interview guides, character questionnaire sheets, and product validation sheets. Data analysis techniques were carried out qualitatively and quantitatively. The results of the study indicate that the R&D research method with the ADDIE model has been developed based on validation by two lecturers and two fifth grade elementary school teachers. The quality of the open module product validation was obtained with an average score of 3.60 (very good category). The implementation of the learning module has an impact on improving students' critical reasoning character from the initial questionnaire with an initial score of 1.92 (low category) to 3.71 (high category), with an increase of 1.79. Meanwhile, the independent character score increased from 1.99 (low category) to 3.60 (high category), with an increase of 1.61. This study shows that the PjBL based Pancasila Education learning module can improve the critical reasoning character and independence of fifth-grade elementary school students. Therefore, this PjBL based Pancasila Education learning module shows quality and is suitable for use.